Consistent Quantitative Operational Risk Measurement and Regulation : Challenges of Model Specification, Data Collection and Loss Reporting - Jobst, Andreas (IMF Working Papers; Working Paper ;, 2007)
Amid increased size and complexity of the banking industry, operational risk has a greater potential to transpire in more harmful ways than many other sources of risk. This paper provides a succinct overview of the current regulatory framework of operational risk under the New Basel Capital Accord with a view to inform a critical debate about the influence of varying loss profiles and different methods of data collection, loss reporting, and model specification on the reliability of operational risk estimates and the consistency of risk-sensitive capital rules. The presented findings offer guidance on enhanced market practice and more effective prudential standards for operational risk measurement.